Exploring the frontiers of eye tracking research in language studies : a novel co-citation scientometric review - Aryadoust, Vahid (2021)
Eye tracking technology has become an increasingly popular methodology in language studies. Using data from 27 journals in language sciences indexed in the Social Science Citation Index and/or Scopus, we conducted an in-depth scientometric analysis of 341 research publications together with their 14,866 references between 1994 and 2018. We identified a number of countries, researchers, universities, and institutes with large numbers of publications in eye tracking research in language studies. We further discovered a mixed multitude of connected research trends that have shaped the nature and development of eye tracking research. Specifically, a document co-citation analysis revealed a number of major research clusters, their key topics, connections, and bursts (sudden citation surges). For example, the foci of clusters #0 through #5 were found to be perceptual learning, regressive eye movement(s), attributive adjective(s), stereotypical gender, discourse processing, and bilingual adult(s). The content of all the major clusters was closely examined and synthesized in the form of an in-depth review. Finally, we grounded the findings within a data-driven theory of scientific revolution and discussed how the observed patterns have contributed to the emergence of new trends. As the first scientometric investigation of eye tracking research in language studies, the present study offers several implications for future research that are discussed.